Pengenalan Plat Kendaraan Otomatis Berbasis Citra Menggunakan Metode Optical Character Recognition (OCR) - Ginting, Rudolf F.A.; Djawas, Julaica F.; Kaesmetan, Yampi R. (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2024)
Automatic parking registration has become a focal point in the research and development of modern urban transportation systems. In this context, image-based vehicle license plate recognition plays a vital role in facilitating efficient and accurate parking registration processes. This research aims to develop an image-based vehicle license plate recognition system for automatic parking registration applications using Optical Character Recognition (OCR) technology. The methods employed include vehicle image acquisition, image preprocessing, license plate segmentation, text extraction using OCR, and license plate character recognition. Testing was conducted using a dataset of vehicle images captured under various lighting conditions and angles. Experimental results demonstrate that the proposed system is capable of recognizing vehicle license plates with a high level of accuracy, even under varying lighting conditions and distorted license plates. Implementation of this system is expected to enhance efficiency in automatic parking registration and reduce manual involvement in the process.